Regional and age-dependent changes in ubiquitination in cellular and mouse models of spinocerebellar ataxia type 3 - Luo, Haiyang; Todi, Sokol V.; Paulson, Henry L.; Costa, Maria do Carmo (Frontiers in Molecular Neuroscience, 2023)
Spinocerebellar ataxia type 3 (SCA3), also known as Machado–Joseph disease, is the most common dominantly inherited ataxia. SCA3 is caused by a CAG repeat expansion in the ATXN3 gene that encodes an expanded tract of polyglutamine in the disease protein ataxin-3 (ATXN3). As a deubiquitinating enzyme, ATXN3 regulates numerous cellular processes including proteasome- and autophagy-mediated protein degradation. In SCA3 disease brain, polyQ-expanded ATXN3 accumulates with other cellular constituents, including ubiquitin (Ub)-modified proteins, in select areas like the cerebellum and the brainstem, but whether pathogenic ATXN3 affects the abundance of ubiquitinated species is unknown. Here, in mouse and cellular models of SCA3, we investigated whether elimination of murine Atxn3 or expression of wild-type or polyQ-expanded human ATXN3 alters soluble levels of overall ubiquitination, as well as K48-linked (K48-Ub) and K63-linked (K63-Ub) chains. Levels of ubiquitination were assessed in the cerebellum and brainstem of 7- and 47-week-old Atxn3 knockout and SCA3 transgenic mice, and also in relevant mouse and human cell lines. In older mice, we observed that wild-type ATXN3 impacts the cerebellar levels of K48-Ub proteins. In contrast, pathogenic ATXN3 leads to decreased brainstem abundance of K48-Ub species in younger mice and changes in both cerebellar and brainstem K63-Ub levels in an age-dependent manner: younger SCA3 mice have higher levels of K63-Ub while older mice have lower levels of K63-Ub compared to controls. Human SCA3 neuronal progenitor cells also show a relative increase in K63-Ub proteins upon autophagy inhibition. We conclude that wild-type and mutant ATXN3 differentially impact K48-Ub- and K63-Ub-modified proteins in the brain in a region- and age-dependent manner.